Measurement of interlaminar shear properties of pultruded CFRP composites based on modified DNS specimens - Yi-Feng Gao; Dong-Dong Zhang; Xiao-Qiang Yan; Fei Li; Tao Yang; Li-Gang Peng (Case Studies in Construction Materials, 2024)
A double-notch shear (DNS) test was modified for a measurement of interlaminar shear properties of pultruded carbon-fibre-reinforced polymer (CFRP) composites under moderate through-thickness compressive stresses, which were applied by torqued bolts. A range of failure criteria were presented to compare with experimental results. An attempt was made to predict the shear stress-strain relationship in the combined stresses with through-thickness compressive and shear stresses. Results indicate that the modified 2DNS specimen makes the shear surface of the specimen more uniform and reduces the peel stress at the notch tip. The 2DNS fixture made it easier to study the influence of composite interlaminar shear strength and shear stress-strain relationship under moderate through-thickness compression. The initial shear stiffness was not affected by moderate through-thickness compressive stresses. Moderate through-thickness compressive stresses on pultruded CFRP materials can increase interlaminar shear strength and ductility. Of all the failure criteria, the Mohr-Coulomb criterion was preferred to predict the enhancement of the shear strength under moderate through-thickness compression. Based on the Mohr-Coulomb criterion and the inverse solution of Ramberg-Osgood model, a unified equation was proposed and can effectively characterise the interlaminar shear stress-strain relationship under moderate through-thickness compression.